Structure of sialylated fucosyl lactosaminoglycan isolated from human granulocytes. - Fukuda,M; Spooncer,E; Oates,JE; Dell,A; Klock,JC (J Biol Chem, 1984)
Sialylated fucosyl lactosaminoglycan was isolated from human neutrophilic granulocytes and its structure was elucidated. The lactosaminoglycan glycopeptides were digested by endo-beta-galactosidase and "the core portion" and released oligosaccharides were analyzed by permethylation, fast atom bombardment mass spectrometry, and exoglycosidases. In addition, lactosaminoglycan saccharides were obtained by hydrazinolysis and the structures of fractionated sialyl oligosaccharides were analyzed by fast atom bombardment mass spectrometry and permethylation coupled with exoglycosidase treatment. The structure of one of the major components was found to be: (Formula: see text). This structure is unique in that 1) four linear polylactosaminyl side chains are attached to the core portion, 2) the side chain arising from position 4 of 2,4-linked mannose contains one or more alpha 1----3 fucosyl residues, 3) the side chain arising from position 6 of 2,6-linked mannose is terminated with NeuNAc alpha 2----3Gal(Fuc alpha 1----3)GlcNAc, sialyl Lex, and 4) the side chain arising from position 2 of 2,4-linked mannose is terminated with sialic acid through alpha 2----6 linkage.